SERIAL VERB CONSTRUCTIONS IN SASAK LANGUAGE OF MENO-MENE DIALECT: A TYPOLOGY AND LFG APPROACH - Sartika Hijriati (Universitas Teknologi Mataram, 2018)
ABSTRACTThis paper aims to analyze the semantic types, the characteristics, and the constituent structure and functional structure of Sasak serial verb constructions. The theory of Typology and Lexical Functional Grammar (LFG) were used to analyze the data. The data in this research were taken from the uttarances of speakers of meno-mene dialect of Sasak. This study is designed as a descriptive qualitative research. The data were collected through observation, interview, and reflective-introspective methods with recording and elicitation techniques. The results show that Sasak serial verb constructions have ten semantic types, which are motion, direction, instrument, comitative, manner, aspect and mood, benefactive, causative, cause-effect, and synonym. Based on the phonological, morphological and syntactical characteristics, Sasak serial verb constructions have the following characteristics: (1) They fall under one intonation contour, 2) They form mono-clause as a single predicate, 3) They have verb markers that occur only on one verb or each verb obtains the same marker, 4) They share aspect, mood, negation, and 5) They share the same arguments. The analysis of constituent structure and functional structure shows that Sasak serial verb constructions have V-V stucture, and X-COMP or X-ADJ structure.Penelitian ini bertujuan menganalisis tipe-tipe semantik, ciri-ciri, dan struktur konstituen dan struktur fungsional pada konstruksi verba serial Bahasa Sasak. Teori yang digunakan untuk menganalisis data adalah teori tipologi dan tata bahasa leksikal fungsional. Penelitian ini dirancang sebagai penelitian deskriptif kualitatif. Pengumpulan data pada penelitian ini menggunakan metode observasi, wawancara dan introspektif-reflektif dengan teknik rekam dan pancing. Hasil analisis menunjukkan konstruksi verba serial bahasa Sasak memiliki sepuluh tipe semantik untuk menunjukkan gerakan, arah, instrumen, komitatif, kecaraan, aspek dan modal, benefaktif, kausatif, sebab-akibat, dan sinonim. Berdasarkan ciri-ciri fonologis, morfologis dan sintaksis, verba serial Bahasa Sasak memiliki ciri: 1) konstruksi verba serial Bahasa Sasak dilafalkan dalam satu intonasi, 2) konstruksi verba serial Bahasa Sasak ialah monoklausa dan berperilaku sebagai predikat tunggal, 3) pemarkah verba serial Bahasa Sasak pada salah satu atau tiap-tiap verba dengan pemarkah yang sama, 4) verba serial Bahasa Sasak berbagi aspek, modal dan negasi, dan 5) verba serial Bahasa Sasak berbagi argumen dalam konstruksinya. Analisis terhadap struktur konstituen dan struktur fungsional menunjukkan verba serial bahasa Sasak memiliki stuktur V-V dan struktur X-KOMP atau X-ADJ.Keywords: serial verb constructions, Sasak, typology, Lexical Functional Grammar